Application of renormalization to potential scattering - deAraujo, C. F.; Tomio, L.; Adhikari, S. K.; Frederico, T. (Iop Publishing Ltd, 1997)
A recently proposed renormalization scheme can be used to deal with nonrelativistic potential scattering exhibiting ultraviolet divergence in momentum space. A numerical application of this scheme is made in the case of potential scattering with r(-2) divergence for small r, common in molecular and nuclear physics, by using cut-offs in momentum and configuration spaces. The cut-off is finally removed in terms of a physical observable and model-independent result is obtained at low energies. The expected variation of the off-shell behaviour of the t-matrix arising from the renormalization scheme is also discussed.